Criminal violence associated to mental health in Salvadorian people - Gutiérrez Quintanilla, José Ricardo (2014)
This is an ex post facto study with a retrospective and cross sectional design, consisting of a random sample of 1,143 participants (538 men and 605 women), age range 17-56 or more. The measures used involved the Escala de estrés y ansiedad delincuencial, and the Cuestionario de salud general. Results revealed that approximately three fourths of the simple considered that the criminal violence context affected their mental health. Differences between men and women were established. Women and urban residents exhibited a greater number of stress symptoms and criminal anxiety. Recommendations for future studies are suggested.